CONSTRUCTING DAGARA GYIL PEDAGOGY: THE LEGACY OF BERNARD WOMA - Vercelli, Michael B. (International Library of African Music, 2020)
Bernard Woma (1966–2018) was a virtuoso musician and global ambassador of Dagara music. From his extensive outreach, workshops, and touring, Bernard’s work teaching the Dagara gyil (xylophone) around the world is recognisable through his detailed compositions emphasising the use of Dagara musical forms. His founding of the Dagara Music Center in Medie, Ghana in 2000, provides instruction on Ghanaian music and dance to hundreds of non-Ghanaian students. Bernard’s pedagogical pieces for gyil introduce Dagara music systematically, building students’ technique and facility on the instruments in addition to ensuring student comprehension of Dagara musical practice. Based on sixteen years of apprenticeship with Bernard, this article investigates his pedagogy, detailing his methodical process through his use of cultural and educational scaffolding techniques theorised as “deliberate practice” by Ericsson and Pool (2016) and underscores the importance of recognising the individual African musician in academic and educational settings.
Keywords: Musical instruments; Education; Pedagogy; Dagara (Music); Gyile (Instrument); African Music